The Implementation of Contextual Learning to Enhance Biology Students’ Critical Thinking Skills - Bustami, Y.; Syafruddin, D.; Afriani, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
One of the life skills exceedingly be required in the globalization era is critical thinking skills; therefore, every level of education has a role in enhancing critical thinking skills of students, especially biology students’. This research aimed to determine the efforts to enhance the critical thinking skills of students’ in biology subject through a Contextual Teaching and Learning (CTL). This research used a quasi-experimental method with a total sample of 62 X grade students at SMA Negeri 4 Sintang. The data of critical thinking skills were obtained from pre- and post-test results with essay test instruments. The data were analyzed descriptively employing an inferential statistic with T-test. The inferential statistical analysis revealed that there was a difference in the critical thinking skills between the CTL learning and the expository learning (t = 5.98>1.83). The posttest average score of students’ critical thinking skills in the CTL learning was 82.56 and categorized as very good. The post-test average score in the expository learning was 68.37 and categorized as fair. The average score of critical thinking skills in the CTL learning increased by 36.06 while the average score of critical thinking skill in the expository learning increased by 19.42. The results of this research concluded that CTL learning was better to enhance the critical thinking skills of students’ in biology subject on the learning material of environmental pollution.